Model of TSL-centers in Li₂B₄O₇:A (A = Cu, Ag) single crystals - Adamiv, V.T.; Antonyak, O.T.; Burak, Ya.V.; Pidzyrailo, M.S.; Teslyuk, I.M. (Functional Materials, 2005)
Basing on spectral studies of the transmission and thermostimulated luminescence of LТВ:А single crystals (А = Cu, Аg), a new mechanism has been proposed to explain the formation of TSL centers therein, so-called А⁰ centers, involving the growth defects of the foreign boron-oxygen complexes. The TSL emission occurs via the energy transfer to a self-localized exciton followed by emissive annihilation thereof. По результатам спектральных исследований пропускания и термостимулированной люминесценции монокристаллов ТБЛ:А (где А = Cu, Аg) предложен новый механизм формирования в них ТСЛ-центров, так называемых А⁰-центров, с участием ростовых дефектов типа "чужих" борокислородных комплексов. ТСЛ излучение происходит через механизм передачи энергии автолокализированному экситону с его последующей аннигиляцией с излучением. 3а результатами спектральних дослiджень пропускання i термостимульованої люмiнесценцiї монокристалiв ТБЛ:А (де А = Cu, Аg) запропоновано новий механiзм формування в них ТСЛ-центрiв, так званих А⁰-центрiв, з участю ростових дефектiв типу "чужих" борокисневих комплексiв. ТСЛ випромiнювання вiдбувається через механiзм передачi енергiї автолокалiзованому екситону з його наступною анiгiляцiєю з випромiнюванням.